Subcorneal Pustular Dermatosis in Childhood: A Case Report and Review of the Literature - Massimiliano Scalvenzi; Franco Palmisano; Maria Carmela Annunziata; Ernesto Mezza; Immacolata Cozzolino; Claudia Costa (Case Reports in Dermatological Medicine)
Subcorneal pustular dermatosis (SCPD, also known as Sneddon-Wilkinson disease) is a rare, benign, chronic, sterile pustular eruption which usually develops in middle-age or elderly women; it is rarely seen in childhood and adolescence. The primary lesions are pea-sized pustules classically described as half-pustular, half-clear flaccid blisters. Histologically the most important feature is a subcorneal accumulation of neutrophils with the absence of spongiosis or acantholysis, although acantholysis may be reported in older lesions. In this paper we present the case of a 7-year-old boy diagnosed with SCPD based on the characteristic clinical and histological features. Dapsone has been successfully used in the treatment of the disease.